Wear properties of graphene-reinforced aluminium metal matrix composite: A review - Salleh, Mohd Shukor; Omar, Mohd Zaidi; Wakhi Anuar, Nur Farah Bazilah; W. Zamri, Wan Fathul Hakim; Md Ali, Afifah; Samat, Saziana (Walter de Gruyter GmbH, 2023)
The recent advancement in graphene-reinforced aluminium matrix composites improves wear behaviour in the production of lightweight and high-performance nano-composites. Considerable works have been devoted to using graphene nanoparticles as solid self-lubricants to increase wear resistance, minimise friction coefficients, improve service efficiency, and extend the lifespan of related sliding components. In general, wear behaviour often depends on the homogeneous distribution of graphene in the aluminium matrix. The non-uniform distribution of reinforcement due to the tendency of graphene to agglomerate in aluminium matrix and its poor wettability becomes a challenge in developing optimum functional of composites. The wettability of graphene can be enhanced by proper processing methods and sufficient addition of magnesium that can improve the wear and frictional properties of the produced composites. Hence, this review article provides recent findings and the influence of graphene as reinforcement materials in composites, including the effects on wear behaviour and friction properties. This article also discusses new advancements in the effect of graphene in self-lubricating aluminium matrix composites and the impact of reinforcement on the wear mechanisms of the composites. The future direction of the wear properties of MMCs is also covered at the end of the revi